OBSTETRIC VIOLENCE: NECESSARY DIALOGUES - Antunes Aquino Cardoso Gonçalves, Sueli; Teixeira Mendes, Simone; Cordeiro Muniz Silva, Elisabete; Rodrigues Santos Guimarães, Junivever; Beatriz Lima Pimenta, Márcia; Rocha Amaral, Adriana; Clara Lélis Ramos Cardoso, Maria; Alencar Froes, Karine; Verkruessen, Fernanda; Marques Bigliazzi, Letícia; Parissa Bondan Misaghi, Mirela; Souza Guerrer, Lara; et al. (Revista Gênero e Interdisciplinaridade, 2026)
Obstetric violence is an important issue that has gained prominence today, with the institutionalization of childbirth, changing into a pathological event. This theme is a form of gender violence, understood as actions performed by health professionals, whether physical or verbal, which annul the autonomy of women in decisions about their bodies and their reproductive process, through a dehumanizing assistance, the abuse of medicalization and pathologization of natural processes. Nurses have gained space in women’s health care because they are the professionals who are closest to the parturient woman. The present article has as its object the bibliographic research that is considered the foundation of any research, in addition, it aims at a familiarity with the theme and the improvement of ideas in the search for the identification of factors, levels, and facts that contribute to the phenomenon of obstetric violence. Thus, this theme does not end with this work, since there are multiple aspects to be evaluated and investigated today.